HUBUNGAN REACTION TIME DAN POWER LENGAN DENGAN KECEPATAN BOLA HASIL SMASH PADA PERMAINAN TENIS MEJA - Januar Ramadhan (Jurnal Sporta Saintika, 2020)
This research is motivated by the importance of physical components to the results of the speed of the smash on table tennis including reaction time and arm power. The purpose of this study was to determine the relationship between reaction time and arm power with the speed of a smash ball in a table tennis game. This study uses a correlational research method. The sample in this study were active members of the Jabung Garut club. A total of 20 samples were taken using purposive sampling technique. The instruments used in this study are the ruler drop test to measure the speed of reaction time and the softball throw test to measure arm power. Data analysis used Statistical Product for Social Science (SPSS) version 22. The results of data analysis showed that there was a significant relationship between reaction time and the smash ball speed, which was p = 0.000 <0.05 with a value of r = -0.719, while the relationship between arm power and ball speed smash results p = 0.001 <0.05 which means there is a significant relationship, and the relationship between reaction time and arm power together with the ball speed smash results produce a significant relationship with the significance of 0.001 <0.05 and r = 0.547. From these results it can be concluded that there is a significant relationship between reaction time and arm power with the speed of the ball smash in table tennis. Keywords: Table Tennis, Smash Ball, Reaction Time, Arm Power